Treatment of Muellerius Capillaris infection in goats - ΧΕΙΜΩΝΑΣ Χ. Α.; ΧΑΡΑΛΑΜΠΙΔΗΣ Σ. Θ.; ΛΙΑΚΟΣ Β. Δ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The anthelminthic efficacy of Albendazole, Febendazole and Levamisole at 10 mg/kg b.w., and Mebendazole at 40 mg/kg b.w. against M. capillaris infection in goats was investigated by comparing the learval counts, done by two different methods, on day, 0, 4 and 8 after treatment. Each drug was administered to 20 animals of a naturally infected flock, while 20 more goats were used as controls. Depending on the method of fecal examination applied, Albendazole treatment afforded 97, 8%-98,8% reduction of larva output, Febendazole 87,93%-92,9% reduction, Levamisole 40,03%-64,05% reduction and Mebendazole 97,68%-98,85% reduction. Control animals showed either an increase of larva output up to 19,37% or a slight reduction of 6,49%. A marked improvement of general condition and milk productivity was observed thereafter to all animal treated.